Penile Prosthesis Implantation and Timing Disparities After Radical Prostatectomy: Results From a Statewide Claims Database. Issue 6 (28th March 2020) - Bajic, Petar; Patel, Parth M.; Nelson, Marc H.; Dornbier, Ryan A.; Kirshenbaum, Eric J.; Baker, Marshall S.; Farooq, Ahmer V.; McVary, Kevin T.; Gupta, Gopal N.; Bresler, Larissa
Abstract: Background: Many patients with erectile dysfunction (ED) after radical prostatectomy (RP) improve with conservative therapy but some do not; penile prosthesis implantation rates have been sparsely reported, and have used nonrepresentative data sets. Aim: To characterize rates and timing of penile prosthesis implantation after RP and to identify predictors of implantation using a more representative data set. Methods: The Healthcare Cost and Utilization Project State Inpatient and State Ambulatory Surgery databases for Florida from 2006 to 2015 were used. Patients undergoing RP (2006–2012) were tracked longitudinally for penile prosthesis implantation. Patient and clinical data were analyzed using multivariable logistic regression. Outcomes: The primary outcome was risk-adjusted predictors of prosthesis implantation, and the secondary outcome was predictors of the highest quartile of time between RP and penile prosthesis. Results: Of 29, 288 men who had RP, 1, 449 (4.9%) patients underwent subsequent prosthesis. The mean time from RP to prosthesis was 2.6 years (median: 2.1; interquartile range [IQR]: 1.2–3.5). Adjusted predictors of prosthesis implantation included open RP (odds ratio [OR]: 1.5, P  < .01), African American race (OR: 1.7, P  < .01) or Hispanic ethnicity (OR: 3.2, P  < .01), and Medicare (OR: 1.4, P  < .01) insurance. Oler patients (age >70 years; OR: 0.7, P  < .01) and those from the highest income quartile relative to the lowest (OR: 0.8, P  < .05) were less likely to be implanted. Adjusted predictors of longer RP-to-implantation time (highest quartile: median: 4.7 years; IQR: 3.9–6.0 years) included open RP (OR: 1.78, P  < .01), laparoscopic RP (OR: 4.67, P  < .01), Medicaid (OR: 3.03, P  < .05), private insurance (OR: 2.57, P  < .01), and being in the highest income quartile (OR: 2.52, P  < .01). Clinical Implications: These findings suggest ED treatment healthcare disparities meriting further investigation; upfront counseling on all ED treatment modalities and close monitoring for conservative treatment failure may reduce lost quality of life years. Strengths & Limitations: This study is limited by its use of administrative data, which relies on accurate coding and lacks data on ED questionnaires/prior treatments, patient-level cost, and oncologic outcomes. Quartile-based analysis of income and time between RP and prosthesis limits the conclusions that can be drawn. Conclusion: Less than 5% of post-RP patients undergo penile prosthesis implantation, with open RP, Medicare, African American race, and Hispanic ethnicity predicting post-RP implantation; living in the wealthiest residential areas predicts lower likelihood of implantation compared to the least wealthy areas. Patients with the longest time between RP and prosthesis are more likely to live in the wealthiest areas or have undergone open/laparoscopic RP relative to robotic RP.